The effects of electronic access to scientific literature in the consortium of Turkish university libraries - (:unkn) unknown (EMERALD GROUP PUBLISHING LIMITED, 2007)
Purpose - The paper seeks to provide some insight into the sharp increase in scientific publications originating from Turkish academic and research institutions in the last few years. The underlying reasons - widespread access to literature through electronic databases being the most important - are also investigated. Design/methodology/approach - Although it is difficult to gauge national scientific productivity, the number of publications in electronic databases that index thousands of scientific journals can give some indication. Web of Science is one of these, and it is provided to the Turkish academic community along with several other databases by the national library consortium. Based on the Web of Science data, a comparative analysis was performed to investigate publications originating from Turkey and other countries. Findings - The analysis revealed a sharp increase in publications from Turkish institutions in the last few years. Considering the highest publishing 30 countries out of 190, the increase between 2001 and 2003 is 53.48 percent for Turkey, followed by 34 percent for China and 26.87 percent for South Korea. Research limitations/implications - Although one of the largest databases was analyzed, it is only one of several. Additionally, there are also several other indicators of scientific productivity such as books published and citations received. Originality/value - The paper provides some insight into the importance of library consortia and the efficient literature access they provide to researchers.
Keywords: libraries; publishing; Turkey